Place of enalapril in treatment of patients with systemic lupus erythematosus and systemic sclerosis - L K Kozlova; V V Bagirova (Научно-практическая ревматология, 2003)
Lupus erythematosus (SLE) and systemic sclerosis (SS). Methods. 45 SLE and 44 SS pts were included. Some of them received antirheumatic drugs in combination with enalapril other were treated with antirheumatic drugs only. The pts were examined before and 6-12 months after the beginning of the treatment. Echocardioscopy and biomicroscopy of bulbar conjunctiva vessels were performed in all cases. Results. Treatment with enalapril improved state of all SLE and SS pts. The drug was well tolerated and provided decrease of dyspnoea and edema as well as blood pressure normalization. Most prominent improvement was evident 12 months after the beginning of enalapril treatment. Reduction of left ventricle myocardium hypertrophy, improvement of its diastolic function and reduction of structural changes of bulbar conjunctiva microcirculation were achieved at that time. Conclusion. Enalapril administration in combination with antirheumatic drugs improves state of SLE and SS pts as well as echocardiography and bulbar conjunctiva vessels biomicroscopy results. It can be recommended for treatment of these diseases.